α-Fe2O3 Nanoparticles/Vermiculite Clay Material: Structural, Optical and Photocatalytic Properties - Valášková, Marta; Tokarský, Jonáš; Pavlovský, Jiří; Prostějovský, Tomáš; Kočí, Kamila (Materials (Basel, Switzerland), 2019)
Photocatalysis is increasingly becoming a center of interest due to its wide use in environmental remediation. Hematite (α-Fe2O3) is one promising candidate for photocatalytic applications. Clay materials as vermiculite (Ver) can be used as a carrier to accommodate and stabilize photocatalysts. Two different temperatures (500 °C and 700 °C) were used for preparation of α-Fe2O3 nanoparticles/vermiculite clay materials. The experimental methods used for determination of structural, optical and photocatalytic properties were X-ray fluorescence (ED-XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry (EDS), N2 adsorption method (BET), diffuse reflectance UV-Vis spectroscopy (DRS), photoluminescence spectroscopy (PL) and photocatalytic reduction of CO2, respectively. The data from XRD were confronted with molecular modeling of the material arrangement in the interlayer space of vermiculite structure and the possibility of anchoring the α-Fe2O3 nanoparticles to the surface and edge of vermiculite. Correlations between structural, textural, optical and electrical properties and photocatalytic activity have been studied in detail. The α-Fe2O3 and α-Fe2O3/Ver materials with higher specific surface areas, a smaller crystallite size and structural defects (oxygen vacancies) that a play crucial role in photocatalytic activity, were prepared at a lower calcination temperature of 500 °C.
Keywords: photocatalytic activity; molecular simulation; α-Fe2O3 photocatalysts; clay materials